The effects of gonadal hormones on learning and memory in male mammals: A review - Stuart T. LEONARD, Peter J. WINSAUER (Current Zoology, 2011)
The primary role of the gonadal steroid hormones in mammals is to regulate reproduction and related behaviors; however, both androgens and estrogens are also integrally involved in mediating higher brain function and processes including cognition, neural development, and neural plasticity. In particular, a number of studies show that estradiol modulates dendritic spine growth and synapse density (synaptic plasticity) in the hippocampus of females, and that increased estradiol levels are generally associated with improvements on a variety of learning and memory tasks. While the majority of research has focused on the beneficial effects of estradiol in females, much less attention has been given to testosterone and its effects on learning and memory in males. Similar to estradiol titers in females, testosterone titers in males decline with age, albeit more gradually, and this decline has been correlated with impairment of certain cognitive tasks. Moreover, studies involving both humans and animals indicate that testosterone and its metabolites can augment responding on certain behavioral tasks, depending on the subject’s current hormonal state, the response required, and the stimuli involved (e.g., those involving spatial or nonspatial stimuli). While the exact mechanisms by which testosterone exerts its effects on learning and memory are not fully understood, recent findings suggest that testosterone modulates learning and memory in males through an interaction with the cholinergic system. The overall objective of this review is to discuss studies investigating the role of the gonadal hormones in mediating learning and memory processes in male mammals [Current Zoology 57 (4): 543–558, 2011].